HUBUNGAN METODE MENGAJAR DISKUSI DENGAN HASIL BELAJAR MATA KULIAH KONSEP KEBIDANAN - Fatma Nadia (STIKes Al-Insyirah Pekanbaru, 2018)
Education is a human need throughout life. Educators are required to develop knowledge and skills in improving the quality of education, especially in teaching and learning. Educators should use teaching methods that can make the students active participation in the learning process as a discussion of teaching methods, so that more students are expected to understand and know about the on going learning. This research aims to determine the relationship of teaching methods discussion with the course learning outcomes concept of midwifery in the first semester student at the Academy of Midwifery Sehat Medan. This research is relational with Cross sectional study design, sampling techniques purposive sampling is taken on the specific considerations that the student first semester class C already represents an other class, which is amount 58 respondents. Based on the statistical test is known that the distribution of discussion teaching method adopted by the lecturer had a good response some 47 people (81%). While the distribution of subjects studied midwifery concept most scored B some 32 people (55,2%). Moment and product test results with confidence level (α) = 5% (0,05), obtained results r count = 0,628 greater than r table = 0,254, so the hypothesis that